1974
DOI: 10.1177/154193127401800407
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Improving Visual Inspection Performance

Abstract: a proposed new i n t e g r a t e d d e s i g n procedure f o r i n s p e c t i o n t a s k s t h a t w i l l approach t h e optimal d e s i g n has been formulated. The review o f r e c e n t r e s e a r c h r e s u l t s i n c l u d e s t h e f o l l o w i n g primary v a r i a b l e s : t h e speed o f t h e i t e m p a s s i n g t h e i n s p e c t o r , t h e spacing of items, t h e percentage of d e f e c t i v e i t e m s , t h e i l l u m i n a t i o n l e v e l , t h e cont r a s t between t h e i t e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Broadbent (1963) and Harris (1968) report that inspection accuracy decreases as the rate of defects in the sample being inspected decreases. Purswell and Hoag (1974) observed that frequent breaks in the inspection task (e.g. 5-min breaks for every 30 min of inspection activity) allowed inspectors to maintain a sorting accuracy of 85% throughout the day as compared with a 60% sorting accuracy when breaks were less frequent (e.g.…”
mentioning
confidence: 99%
“…Broadbent (1963) and Harris (1968) report that inspection accuracy decreases as the rate of defects in the sample being inspected decreases. Purswell and Hoag (1974) observed that frequent breaks in the inspection task (e.g. 5-min breaks for every 30 min of inspection activity) allowed inspectors to maintain a sorting accuracy of 85% throughout the day as compared with a 60% sorting accuracy when breaks were less frequent (e.g.…”
mentioning
confidence: 99%
“…Inspectors frequently perform their tasks for prolonged periods of time that can induce vigilance effects. One of the principal recommendations to help prevent the occurrence of a vigilance decrement or reduce its magnitude during visual inspection is to alter the schedule so that inspectors spend no more than 30 minutes at a time inspecting parts (Purswell & Hoag, 1974;Swain, 1967). Colquhoun (1959) and Purswell and Hoag (1974) advocated a five-minute rest break after 30 minutes of inspection work, as opposed to the traditional work/rest schedule of a 15-minute break every four hours, to relieve the perceptual and cognitive demands of inspection.…”
Section: Work/rest Schedulesmentioning
confidence: 99%
“…One of the principal recommendations to help prevent the occurrence of a vigilance decrement or reduce its magnitude during visual inspection is to alter the schedule so that inspectors spend no more than 30 minutes at a time inspecting parts (Purswell & Hoag, 1974;Swain, 1967). Colquhoun (1959) and Purswell and Hoag (1974) advocated a five-minute rest break after 30 minutes of inspection work, as opposed to the traditional work/rest schedule of a 15-minute break every four hours, to relieve the perceptual and cognitive demands of inspection. In Colquhoun's (1959) study of machine-paced visual inspection, for example, inspectors who received a five-minute break after 30 minutes missed an average of 9.9 defects in the second half hour, as compared to an average of 44.1 missed defects in the group that performed continuously for 60 minutes.…”
Section: Work/rest Schedulesmentioning
confidence: 99%